Metabolism of a Bioorthogonal PET Tracer Candidate [F-19/F-18]SiFA-Tetrazine in Mouse Liver Microsomes: Biotransformation Pathways and Defluorination Investigated by UHPLC-HRMS - Otaru S; Niemikoski H; Sarparanta M; Airaksinen AJ (AMER CHEMICAL SOC, 2025)
Organofluorosilicon based F-18-radiolabeling is an efficient method for incorporating fluorine-18 into BF-radiopharmaceuticals for positron emission tomography (PET) by F-19/F-18 isotopic exchange (1E). The first PET radiopharmaceutical, F-18 SiFAlin-TATE, radiolabeled with a silicon-based [F-18]fluoride acceptor (SiFA), namely, a para-substituted di-tert-butyl[F-18]-fluorosilylbenzene, has entered clinical trials, and is paving the way for other potential [F-18]SiFA-labeled radiopharmaceuticals for diagnostic use. In this study, we report the in vitro metabolism of an oxime-linked SiFA tetrazine (SiFA-Tz), a new PET-radiotracer candidate, recently evaluated for pretargeted PET imaging and macromolecule labeling. Metabolism of SiFA-Tz was studied in mouse liver microsomes (MLM) for elucidating its major biotransformation pathways. Nontargeted screening by ultrahigh performance liquid chromatography high-resolution mass spectrometry (UHPLC-HRMS) was utilized for detection of unknown metabolites. The oxime bond between the SiFA and Tz groups forms two geometric (E/Z) isomers, which underwent the same biotransformations, but unexpectedly with different kinetics. In total, nine proposed metabolites of SiFA-Tz from phase I and II reactions were detected, five of which were defluorinated in MLMs, elucidating the metabolic pathway leading to previously reported defluorination of [F-18]SiFA-Tz in vivo. Based on the HRMS studies a biotransformation pathway is proposed: hydroxylation (+O) to tert-butyl group adjacent to the silicon, followed by oxidative defluorination (+OH/-F) cleaving the fluorine off the silicon. Interestingly, eight proposed metabolites of a reduced dihydrotetrazine analogue, SiFA-H,Tz, from phase I and II reactions were additionally detected. To the best of our knowledge, this is the first reported comprehensive investigation of enzyme mediated metabolic pathway of tetrazines and para-substituted di-tertbutylfluorosilylbenzene fluoride acceptors, providing novel structural information on the biotransformation and fragmentation patterns of radiotracers bearing these structural motifs. By investigating the metabolism preceding defluorination, structurally optimized new SiFA compounds can be designed for expanding the portfolio of efficient F-19/F-18 isotopic exchange labeling probes for PET imaging.